SISTEM INFORMASI PENGELOLAAN KEGIATAN DAN PEMBINAAN PENGHUNI ASRAMA WILLIAM BOOTH: - Handiwidjojo, Wimmie; Jek Siang, Jong; Hardiyanto, Purnawan (LPPM Uncen, 2024)
The Salvation Army Cinere Dormitory is a dormitory where most of the residents are prospective Salvation Army chaplains (cadets). The Cinere dormitory is occupied by 82 cadets. The activities carried out by cadets in the dormitory include spiritual formation and doing daily work according to the schedule set by the dormitory management. Data management, practical task scheduling, spiritual formation are all done manually. As a result, historical data is difficult to find when needed, there is often an imbalance in workload among cadets, duplication of work schedule arrangements and a lack of objective assessment of soft skills and cadet personalities. This community service activity goals is to create an information system for managing the activities of Cinere dormitory residents. The methods used were interviews about system requirements, system creation, outreach to partners and evaluation of system usability. The results of the activity are a system that can help dormitory managers in managing cadet activities and digitizing soft skills assessments, as well as a guide to using the system. The system were socialized in October 2023 by providing direct training to dormitory managers and residents. Evaluation of the usability of the system was carried out by distributing questionnaires to 12 cadets, 3 dormitory supervisors and 1 system admin. The evaluation results show a usability level of 87%. It can be concluded that the system created is useful to help manage Cinere dormitory residents.